Membangun kesadaran religius siswa melalui program sekolah di Sekolah Dasar Negeri Pingit Yogyakarta - Dahuri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to describe the strategy implemented by SD Negeri Pingit in building religious awareness in students through the implemented school program. The research method used is qualitative research with a case study approach. Data was collected through participatory observation, in-depth interviews with teachers and school staff, and analysis of documents related to school programs. Data analysis techniques in this study are data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study used a type of triangulation. The results showed that SD Negeri Pingit had implemented a number of effective strategies to build religious awareness in students. The programs carried out include daily habits such as morning prayers, joint tadarus, and religious activities that are integrated into the curriculum. In addition, the school also organizes extracurricular activities that focus on developing religious values, such as prayer groups, religious studies, and religion-based social activities. Teachers also play an active role in providing religious learning, guidance and assistance to students.